2021
DOI: 10.1371/journal.pone.0250781
|View full text |Cite
|
Sign up to set email alerts
|

Designing internet-enabled patient education for self-management of T2D diabetes—The case of the Razavi-Khorasan province in Iran

Abstract: Background The number of people with diabetes is estimated to increase to 642 million by 2040, with most having type 2 diabetes. Patients with diabetes require continuous monitoring and possible treatment changes. Patient education is the process of enabling individuals to make informed decisions about their personal health-related behaviours and internet-enabled interventions have the potential to provide support and information to patients with diabetes. Objective The aim of the study was to design a porta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 40 publications
0
5
0
6
Order By: Relevance
“…In the context of nursing care, they can enhance and qualify care actions, since they help in the process of learning and self-knowledge of the individual regarding their health condition (25) . In the studies identified in this review, the TEs used were: printed technologies (15)(16) ; interactive technologies and mobile applications (18)(19)(20)22) ; telemonitoring (21) ; simulation (17) ; and audiovisual production (14) .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the context of nursing care, they can enhance and qualify care actions, since they help in the process of learning and self-knowledge of the individual regarding their health condition (25) . In the studies identified in this review, the TEs used were: printed technologies (15)(16) ; interactive technologies and mobile applications (18)(19)(20)22) ; telemonitoring (21) ; simulation (17) ; and audiovisual production (14) .…”
Section: Discussionmentioning
confidence: 99%
“…The use of interactive platforms to build care tools was identified in most of the selected studies (18)(19)22) . Along with the importance of interactivity for care, a systematic review highlighted that access to interactive technologies by people with DM has generated positive impacts on changes in habits and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations